Pengembangan Karakter Siswa SD melalui Implementasi Profil Pelajar Pancasila dan Falsafah Tri Hita Karana - ayu astiti, kadek (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Students at the elementary school level are students aged 7 to 12 years. Development during this period is a unique phase starting from physical, social, language, cognitive, moral, emotional, intelligence and character development. At this time, character development is an important part to pay attention to. Good character development will make it easier for students to adapt to the social environment. This research is a literature review. The analytical method used is narrative review analysis. The results of this research show that character education in elementary school students can be formed through the implementation of the Pancasila and Tri Hita Karana student profiles. The six elements of the Pancasil student profile are 1) faith, devotion to God Almighty and noble character, 2) global diversity, 3) independence, 4) mutual cooperation, 5) critical reasoning, 6) creativity. Meanwhile, the 3 aspects of tri hita karana are 1) parahyangan, 2) pawongan, 3) palemahan. Activities that can be carried out to shape character are through the learning process, P5 projects, extracurriculars, and habituation.